2004
DOI: 10.1046/j.1529-8817.2004.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Commingling Analysis of Intraocular Pressure and Glaucoma in an Older Australian Population

Abstract: SummaryPurpose: To test the hypothesis of a major genetic determinant of intraocular pressure (IOP) under the mixed genetic model in a defined population, and to elucidate the relationship between IOP and glaucoma. Methods: IOP was measured in 3654 persons attending the Blue Mountains Eye Study. A commingling analysis on IOP was performed using a new program, SKUDRIVER. The goodness of fit of 1-, 2-and 3-distribution models was measured. This was repeated after the glaucoma cases had been removed from the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In previous work, the researchers estimated 36% heritability for IOP after adjusting for covariates 9. A commingling analysis from the Australian Blue Mountains Eye Study suggested the presence of a major gene contributing to 18% of the variance of IOP 10. Novel genetic loci for IOP have been identified,8 1113 but not yet replicated.…”
mentioning
confidence: 99%
“…In previous work, the researchers estimated 36% heritability for IOP after adjusting for covariates 9. A commingling analysis from the Australian Blue Mountains Eye Study suggested the presence of a major gene contributing to 18% of the variance of IOP 10. Novel genetic loci for IOP have been identified,8 1113 but not yet replicated.…”
mentioning
confidence: 99%
“…This does not seem to be the case in the Blue Mountains Eye Study cohort. Previous commingling analyses on IOP 14 and optic disc morphology 13 do not suggest departure from HWE. Furthermore, a recent study 52 of the complement factor H (CFH) single-nucleotide polymorphism rs1061170 (Y402H) in this cohort identified CC, CT, and TT genotypes in 13.6%, 46.7%, and 39.7% of the population, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…13,14 In brief, the analysis investigates whether the observed distribution of a quantitative trait is best modeled by a single distribution or by an admixture of multiple distributions. A single distribution suggests the lack of a single major genetic determinant for the trait, whereas multiple distributions suggest the presence of a major genetic determinant, especially if the distributions are in HardyWeinberg equilibrium (HWE) for population-ascertained data.…”
mentioning
confidence: 99%
“…However, genetic association studies on primary open-angle glaucoma have had conflicting results or have not been replicated 37. Poor specificity in the currently used phenotype parameters is a possible explanation,37 indicating that glaucoma genetics should focus on quantitative trait locus (QTL) studies, using variables such as intraocular pressure and cup-to-disc ratio 77 78…”
Section: Discussionmentioning
confidence: 99%